1998
DOI: 10.1111/j.1440-1584.1998.tb00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Client Perceptions of a Rural‐based Cardiac Rehabilitation Program: A Grounded Theory Approach

Abstract: A grounded theory approach was used in an attempt to generate theory about client perceptions and experiences of a cardiac rehabilitation program conducted in a rural community. A series of interviews was conducted with a selection of people who had experienced a life-threatening cardiac event. The cohort was divided into two groups: those who attended a cardiac rehabilitation program and those who did not. The findings, though not generalisable, allowed the generation of a number of theories (which may come t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…The importance of health workers' communication in influencing CR attendance has been highlighted previously (Thornhill & Stevens, 1998). While it is not possible to determine (given the retrospective recall by participants) the accuracy or specific content of health professionals' communication, it is the patient's interpretation of this information, and its integration into their individual illness schemas that is interesting.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of health workers' communication in influencing CR attendance has been highlighted previously (Thornhill & Stevens, 1998). While it is not possible to determine (given the retrospective recall by participants) the accuracy or specific content of health professionals' communication, it is the patient's interpretation of this information, and its integration into their individual illness schemas that is interesting.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, qualitative research has indicated that patients may view attendance at cardiac rehabilitation as unnecessary or inappropriate [37]. Specific beliefs leading to this view include a lack of understanding of the role of physical activity in recovery, a lack of awareness of the content of cardiac rehabilitation, and misconceptions about CHD, including the idea that stress or worry was the primary causative factor [5,[38][39][40].…”
Section: Implications For Cardiac Rehabilitation Attendancementioning
confidence: 96%
“…29,39,40,75 The location, convenience and accessibility of a cardiac rehabilitation programme influence attendance. 14,34,41,43,66,76 Patients living closer to the programme are more likely to receive a referral and attend. 37,52,65 Patients living in cities or urban areas are more likely to attend cardiac rehabilitation.…”
Section: Barriers To Uptake and Adherencementioning
confidence: 99%